Avaliação da insegurança alimentar em beneficiários do Programa Bolsa Família do município de Itaqui - RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Our study aimed to evaluate food insecurity in participants of the Brazilian conditional cash transfer program called Bolsa Família in the city of Itaqui, RS. Data collection was carried out in 2017 at the city’s primary health care units, where a questionnaire containing information about socioeconomic and demographic characteristics, anthropometric measures and food consumption was applied. We evaluated food insecurity by using the short version of the Brazilian food insecurity scale, proposed by Santos et al. (2014). We interviewed 116 individuals who average aged 36 years, most of them had white skin color and almost half had 5 to 8 years of formal education. The families were composed, on average, by 3.4 members, 50% of respondents were the head of the family and more than 70% were employed by the time of the study. Additionally, the prevalence of food insecurity was 85%, according to the questionnaire. Regarding Bolsa Familia, we found that the average time of participation in the program was 6.7 years and the average received value was R$ 152.00. When we asked them about participation in professional qualification programs after enrollment in Bolsa Familia, only 12% of them had participated in these kinds of programs. Nevertheless, 77% reported having more involvement in their children's school life and 90% said that children are missing less school classes. We also observed that 52% of the participants reported an improvement in feeding habits, and families who participate in the program for less time and who receive lower value had a lower prevalence of food insecurity, although without statistical difference. Finally, there was no difference in the prevalence of food insecurity among those who reported an improvement in their feeding habits compared to those who did not notice any change. We concluded that the prevalence of food insecurity was high in the participants of Bolsa Familia program grant regardless of the variables evaluated.
Keywords: Segurança alimentar e nutricional; Políticas públicas; Vulnerabilidade social; Food and nutrition security; Public policy; Social vulnerability; CNPQ::CIENCIAS DA SAUDE